Prophetic-based education: Enhancing self-regulated learning in digital era through patience values - Zarkasyi, Azmi; Fadhilah, Linda Dinil; Maulaya, Rosendah Dwi; Mahmudi, Ihwan; Tsabitah, Nurikha Aliefina (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The digital era presents major challenges for students in developing Self-Regulated Learning (SRL), particularly due to digital distractions, an instant gratification culture, and weak self-control. This article aims to conceptually explore how the internalization of the value of patience (ṣabr) within the framework of prophetic education can strengthen students’ SRL abilities. Using a library research method, this study examines literature related to SRL, the Islamic concept of patience, and the prophetic education approach. The results of the study show that prophetic education is the basis that the value of patience has a role in building SRL. The first hadith is related to the value of patience that will bring victory, relevant to goal setting and a gradual learning process. The second hadith, patience is afflicted with difficulties and fatigue will erase sins, relevant to instilling values to always strive to evaluate every learning process even though it is difficult. The third hadith is about the value of patience to control anger, relevant to maintaining internal motivation in learning so that it is not easy to give up when facing difficulties and obstacles. So, students need patience to be able to regulate the difficult learning process. Therefore, strengthening SRL requires not only cognitive strategies but also value-based approaches that address the affective and spiritual dimensions of learners. This article offers a conceptual contribution to the development of an integrative Islamic education model that responds to the challenges of the digital age through a prophetic, value-oriented approach centered on patience. Abstrak Era digital menghadirkan tantangan besar bagi siswa dalam mengembangkan Self-Regulated Learning (SRL), terutama akibat distraksi digital, budaya instan, dan lemahnya pengendalian diri. Artikel ini bertujuan mengkaji secara konseptual bagaimana internalisasi nilai sabar dalam kerangka pendidikan profetik dapat memperkuat kemampuan SRL siswa. Menggunakan metode penelitian kepustakaan, kajian ini menelaah literatur tentang konsep SRL, sabar dalam perspektif Islam, dan pendekatan pendidikan profetik. Hasil kajian menunjukkan pendidikan profetik menjadi dasar bahwa nilai sabar mempunyai peran untuk membangun SRL. Hadist pertama berkaitan dengan nilai sabar yang akan membawa kemenangan, relevan dengan penetapan tujuan dan proses pembelajaran yang bertahap. Hadist kedua, sabar ditimpa kesulitan dan kelelahan akan menghapus dosa, relevan dengan penanaman nilai untuk selalu berikhtiar mengevaluasi setiap proses belajar meskipun hal tersebut sulit. Hadist ketiga, adalah tentang nilai sabar dapat mengendalikan amarah, relevan dengan menjaga motivasi internal dalam belajar agar tidak mudah putus asa apabila menghadapi kesulitan dan hambatan. Sehingga siswa perlu nilai sabar untuk dapat meregulasi proses belajar yang sulit. Dengan demikian, penguatan SRL perlu dilakukan tidak hanya dengan strategi kognitif, tetapi juga melalui pendekatan nilai yang menyentuh aspek afektif dan spiritual peserta didik. Artikel ini memberikan kontribusi konseptual terhadap pengembangan model pendidikan Islam yang integratif, yang menjawab tantangan era digital dengan pendekatan profetik berbasis nilai sabar.